The Impact of Span Width and Outrigger Shape on Fishing Boats at Palabuhanratu Fishing Port, Indonesia - Fikri Rizky Malik; Yopi Novita; Budhi Hascaryo Iskandar; Gondo Puspito; Sri Suryo Sukoraharjo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Outrigger boats are prevalent in Indonesian waters. In Indonesia, the majority of Outrigger boats have a gross tonnage of less than 7 GT, resulting in their classification as